PENGARUH AROMATERAPI LEMON TERHADAP INTESITAS NYERI PADA IBU POST SC DI RS BHAYANGKARA - Anom, Sang Ayu (STIKES ADVAITA MEDIKA TABANAN, 2025)
Intoduction: According to the World Health Organization (WHO), deliveries by caesarean section throughout the world in 2023 will be around 10-15% per 1,000 births in the world. The main problem that arises in post-SC patients is pain. Untreated post-operative pain can result in clinical and psychological changes that impair quality of life. The aim of this study was to determine the effect of lemon aromatherapy on pain in post-cesarean section mothers at Bhayangkara Hospital. Metohds: This study used a quasi-experimental research design with a one group pre-post test design with purposive sampling, which involved 30 pregnant women. Anxiety was measured using the Anxiety Questionnaire related to pregnancy-revision 2 (PRAQ-R2) and then analyzed the data with the Wilcoxon t-test because the data were not normally distributed. Suggestion: The results of the research show that the characteristics of mothers giving birth after SC show that the average age of respondents is 28 years, most respondents have a high school education and the average number of parities is second parity. Analysis of anxiety levels using Wilcoxon obtained a p-value < α (p-value = 0.000, α = 0.05), so H0 was rejected and Ha was accepted, meaning that there was lemon aromatherapy given to the intensity of maternal pain post SC in the treatment group. The results of this research are expected to provide lemon aromatherapy can be used as a consideration in providing midwifery care to reduce pain in post-SC mothers.